Symbiopectobacterium purcellii, gen. nov., sp. nov., isolated from the leafhopper Empoasca decipiens. Issue 6 (13th June 2022) - Nadal-Jimenez, Pol; Siozios, Stefanos; Halliday, Nigel; Cámara, Miguel; Hurst, Gregory D. D.
Abstract : Bacterial endosymbionts are found in multiple arthropod species, where they play crucial roles as nutritional symbionts, defensive symbionts or reproductive parasites. Recent work has highlighted a new clade of heritable microbes within the gammaproteobacteria that enter into both obligate and facultative symbioses, with an obligately required unculturable symbiont recently given the name Candidatus Symbiopectobacterium. In this study, we describe a culturable rod shaped non-flagellated bacterial symbiont from this clade isolated from the leafhopper Empoasca decipiens . The symbiont is related to the transovarially transmitted 'BEV' bacterium that was first isolated from the leafhopper Euscelidius variegatus by Alexander Purcell, and we therefore name the symbiont Symbiopectobacterium purcellii sp. nov., gen. nov. We further report the closed genome sequence for S. purcellii . The genome is atypical for a heritable microbe, being large in size, without profound AT bias and with little evidence of pseudogenization. The genome is predicted to encode Type II, III and VI secretion systems and associated effectors and a non-ribosomal peptide synthase array likely to produce bioactive small molecules. The predicted metabolism is more complete than for other symbionts in the Symbiopectobacterium clade, and the microbe is predicted to synthesize a range of B vitamins. However, Biolog plate results indicate that the metabolism is depauperate compared to the sister clade, represented by Pectobacterium carotovorum . A quorum-sensing pathway related to that of Pectobacterium species (containing an overlapping expI-expR1 pair in opposite directions and a "solo" expR2) is evidenced, and LC-MS/MS analysis reveals the presence of 3-hydroxy-C10-HSL as the sole N -acylhomoserine lactone (AHL) in our strain. This AHL profile is profoundly divergent from that of other Erwinia and Pectobacterium species which produce mostly 3-oxo-C6- and 3-oxo-C8-HSL and could aid group identification. Thus, this microbe denotes one that has lost certain pathways associated with a saprophytic lifestyle but represents an important baseline against which to compare other members of the genus Symbiopectobacterium that show more profound integration into host biology. The type strain of Symbiopectobacterium purcellii gen. nov., sp. nov. is SyEd1 T (LMG 32449 T =CECT 30436 T ).